2000
DOI: 10.1098/rsta.2000.0579
|View full text |Cite
|
Sign up to set email alerts
|

The effect of thermal core–mantle interactions on the palaeomagnetic secular variation

Abstract: We compare a numerical dynamo model with a model of the palaeosecular variation and nd that, although there is good agreement in the meridional distribution of the secular variation, the amplitude of secular variation in the dynamo model is too small. Increasing the Rayleigh number does little to increase the amplitude of the secular variation, while it increases the axial dipole component of the eld to geophysically unreasonably large values. However, by introducing lateral variations in heat ®ux across the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 31 publications
1
34
0
Order By: Relevance
“…Of particular interest is the regime in which the fluid flow and magnetic field become locked to the boundary anomalies because this can explain the observation of the four relatively stationary main concentrations of flux seen on the surface of the Earth's core. Both papers used the pattern of seismic shear wave velocity at the base of the Earth's mantle for the heat flow boundary condition, in common with several previous studies , Bloxham 2000, Olson and Christensen 2002, Christensen and Olson 2003. Paper I found a near-steady solution with surface magnetic flux concentrated into four main lobes located very close to those in the Earth.…”
Section: Introductionmentioning
confidence: 53%
“…Of particular interest is the regime in which the fluid flow and magnetic field become locked to the boundary anomalies because this can explain the observation of the four relatively stationary main concentrations of flux seen on the surface of the Earth's core. Both papers used the pattern of seismic shear wave velocity at the base of the Earth's mantle for the heat flow boundary condition, in common with several previous studies , Bloxham 2000, Olson and Christensen 2002, Christensen and Olson 2003. Paper I found a near-steady solution with surface magnetic flux concentrated into four main lobes located very close to those in the Earth.…”
Section: Introductionmentioning
confidence: 53%
“…Depending on the amount of radiative conduction, the conductive component to the heat loss across the CMB is thus uncertain by (at least) a factor of two (Q cmb ≈ 7.5 to 15 TW). It is likely, however, that the flux into the base of the mantle exceeds the heat conducted down the core adiabat, which has implications for models of thermal coremantle coupling, core evolution, and the distribution of heat-producing elements (36,37).…”
Section: D′′ Structure and Temperaturementioning
confidence: 99%
“…The dynamically self-consistent models of Bloxham (2002) supported this. Bloxham (2000), also using the tomographic model of Masters et al (1996), was able to match numerical and observed magnitudes of secular variation (SV). He found a rapid increase in SV near the equator but no average difference in SV between the Pacific and Atlantic hemispheres.…”
Section: Introductionmentioning
confidence: 99%